Radiotherapy and Erlotinib Combined: Review of the Preclinical and Clinical Evidence - Mehta, Vivek K. (Frontiers in Oncology, 2012)
Epidermal growth factor receptor is often overexpressed in tumors and has been associated with poor prognosis in some cancer types. The introduction of inhibitors of epidermal growth factor receptor, such as erlotinib and cetuximab, represents an important recent advance in the targeted treatment of cancer. Several studies have evaluated inhibitors of epidermal growth factor receptor in combination with radiotherapy, and a strong biologic rationale exists for the use of this combination in certain cancer types, including head and neck squamous cell carcinoma, non–small cell lung cancer, glioblastoma, esophageal cancer, and pancreatic cancer. Preclinical and clinical studies are underway to evaluate the combination of epidermal growth factor receptor inhibitors with radiotherapy. To date, the results suggest that this approach is at least feasible and may result in modest improvement in outcomes compared with either modality alone.